ANALISIS PENDAPATAN DAN STRATEGI PENGEMBANGAN USAHA BUDIDAYA LEBAH MADU DI DESA KECAPI KECAMATAN KALIANDA KABUPATEN LAMPUNG SELATAN (STUDI KASUS DI KEBUN LEBAH SIMPUR) - Fathan Sabrina; Bustanul Arifin; Dewi Mulia Sari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
This study analyzed income levels, identified business development strategies, and formulated priority strategies for honey bee farm at the Kebun Lebah Simpur. The research method used was a case study with a location deliberately chosen at the Kebun Lebah Simpur, Kecapi Village, Kalianda District, South Lampung Regency. Data collection was conducted in May 2025, involving five respondents consisted  of the owner, two production employees, and two consumers. Income analysis was performed using the R/C ratio analysis. Business development strategies were analyzed using the Business Model Canvas (BMC) method, followed by SWOT and QSPM analyses. The results showed that: (1) The honey bee farm business at Kebun Lebah Simpur was feasible because  the R/C ratio score was  8,26 on cash costs,  and  the R/C ratio  on  total costs was 4,21 ,  the income on cash costs was  IDR 77.876.700/year and income on total costs was  IDR 674.672.533/year. (2) The combination of BMC and SWOT analysis resulted  a total weight score of 3,495 on the IFE matrix and 3,208 on the EFE matrix, placing the honey bee farm business at Kebun Lebah Simpur in quadrant I. Thisindicated a growth and profitable strong business position. Therefore, the appropriate business development strategy was market and product development.  (3) An alternative strategy that could be prioritized was maximizing agrotourism activities as an educational medium related to products, increasing visibility, and simultaneously as a product branding medium to build long-term consumer loyalty. Key words:  Business Income, Business Model Canvas (BMC), Development Strategy, Honeybees